Maxillary sinus volume changes in individuals with different craniofacial skeletal patterns: CBCT study - Kevser Dinç; Derya İçöz (BMC Oral Health)
Abstract Background The maxillary sinus, which is crucial for craniofacial growth, is the largest and earliest sinus to develop among the paranasal sinuses. Our study aimed to evaluate the maxillary sinus volume (MSV) in individuals with different sagittal skeletal patterns via cone beam computed tomography (CBCT). Materials and methods In this study, CBCT images of 106 retrospectively selected patients (62 females and 42 males) were included. The ANB and SNA angles were measured to determine the skeletal pattern and position of the maxilla in the sagittal direction. Patients were divided into three groups according to ANB angle: Class I (ANB 2°±2°), Class II (ANB˃4°), and Class III (ANB < 0°). The position of the maxilla in the sagittal direction was divided into three groups according to the SNA angle: normal (SNA 82°±2°), retrognathic (SNA < 80°) and prognathic (SNA˃84°). The MSV was measured by two observers and the data obtained were statistically analyzed. Results The mean age of the participants was 22.5 ± 4.32. The mean MSV was 28.598 ± 7.9 cm3 in females and 34.231 ± 8.93 cm3 in males. The difference between the sexes was statistically significant in terms of MSV (p < 0.001). When the MSV was compared according to different skeletal patterns and positions of the maxilla, no statistically significant difference was detected between the SNA groups (p = 0.650) and the ANB groups (p = 0.905). Conclusions Different skeletal patterns and positions of the maxilla in the sagittal direction do not significantly change the MSV, but compared with sex, the MSV is greater in males than in females. The outcomes of this study may be beneficial in the context of dental interventions such as orthodontics and maxillofacial surgery. Clinical trial number Not applicable.